Evaluasi Usability Pada Aplikasi Teman Bus Menggunakan Metode System Usability Scale dan Heuristic Evaluation - Yuniati, Trihastuti; Christiawan, Dhamara Alan (Direktorat Riset dan Pengabdian Pada Masyarakat (DRPM) Universitas Bina Darma, 2024)
Abstract : Teman Bus application is one form of digital development utilized to support Teman Bus transportation services. Based on comments found on the Google Play Store, users have encountered difficulties when using the application. Additionally, observations of the application have revealed several interface-related shortcomings, indicating the need for usability evaluation. The System Usability Scale (SUS) method was employed to evaluate the user perspective, while the Heuristic Evaluation (HE) method was used to evaluate from the expert perspective. The evaluation results showed an SUS score of 60.225 for the Teman Bus application, which falls into the